1991
DOI: 10.1016/s0022-5347(17)37940-5
|View full text |Cite
|
Sign up to set email alerts
|

Complication of a Penile Prosthesis Reservoir: Venous Compression Masquerading as a Deep Venous Thrombosis

Abstract: We report a case of vascular compromise secondary to the reservoir of an inflatable penile prosthesis. The problem masqueraded as deep venous thrombosis in the lower extremity of a patient 3 years after a spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…4,5 The complication of a ureteral compression leading to hydronephrosis by a retained reservoir has never been reported in literature to date, while a case of venous compression by a functioning reservoir was ever reported. 6 In our case, in addition to the inflammatory change around the reservoir, the fluid in the reservoir also had some contribution to the bulky effect, which lead to compression of the ureter. Therefore, evacuation of fluid in the reservoir during explantation of penile implant should be emphasized to minimize the bulky effect, which might compress adjacent organs.…”
Section: Discussionmentioning
confidence: 59%
“…4,5 The complication of a ureteral compression leading to hydronephrosis by a retained reservoir has never been reported in literature to date, while a case of venous compression by a functioning reservoir was ever reported. 6 In our case, in addition to the inflammatory change around the reservoir, the fluid in the reservoir also had some contribution to the bulky effect, which lead to compression of the ureter. Therefore, evacuation of fluid in the reservoir during explantation of penile implant should be emphasized to minimize the bulky effect, which might compress adjacent organs.…”
Section: Discussionmentioning
confidence: 59%
“…Vascular injury during or following placement of a reservoir is certainly possible during the digital or sharp dissection to enter the space of Retzius, as the external iliac system is in close proximity. Five cases including the one noted in this article have been reported, where pressure of the reservoir caused subsequent partial venous obstruction with subsequent lower extremity edema [34][35][36][37]. Brison et al reported a case of a 51-year-old man with a prior history of radiation therapy and large bowel diversion for rectal cancer who underwent IPP placement.…”
Section: Vascular Injurymentioning
confidence: 79%
“…With traditional reservoir placement in the space of Retzius, iliac vein compromised by laceration or reservoir pressure causing thrombosis has been reported in the literature on multiple occasions [7–10]. Previous pelvic surgery, as noted in these reports, obviously alters the surgical planes and makes the injury more likely.…”
Section: Discussionmentioning
confidence: 91%